A proposal to account for the stimulus, the mechanism, and the mediators released in exercise-induced bronchoconstriction - Anderson, Sandra D.; Kippelen, Pascale (Frontiers in Allergy, 2023)
Exercise-induced bronchoconstriction (EIB) is the name used to describe the transient narrowing of the airways that follows vigorous exercise. It most commonly occurs in children and adults with asthma and in elite athletes. (1, 2) From early controversies about the primary stimulus of EIB (i.e. loss of water versus loss of heat from the airways as a result of conditioning of large volumes of inhaled air during exercise-hyperpnea) (3) to the establishment of the mechanism of EIB (i.e. bronchial smooth muscle contraction in response to an osmotic-driven inflammation in the lower airways) (4) and subsequent identification of specific mediators involved (i.e. histamine, prostaglandins and leukotrienes) (5-10), significant progress has been made in the field over the past 50 years. Herein we summarise (with the use of select illustrations) our current understanding of the stimulus, mechanism and mediators released in EIB.